Pembingkaian Berita Gimik Gibran Rakabuming dalam Debat Pilpres Keempat: Analisis Framing Robert N. Entman pada Media Online Tempo.Co dan Rmol.Id Periode Januari 2024 - Abyansyah, Hikmal Abraar; Ahmad Zamzamy (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze how online media Tempo.co and RMOL.id framed news related to Gibran Rakabuming's gimics in the vice presidential candidate debate in January 2024. Using qualitative research methods and Robert N. Entman's framing analysis approach, this research explores the different perspectives of the two media in presenting reality. The results showed that Tempo.co framed Gibran's gimik as impolite and unnecessary, emphasizing the negative aspects and showing the impropriety of Gibran's behavior. In contrast, RMOL.id viewed the gimik as a brave act that reflected the expression and courage of young people. The differences in the reporting of the two media reflect the construction of reality influenced by each media's preferences and perspectives. This research emphasizes that news is not a pure reflection of reality, but rather a construction that depends on the media's point of view. The findings underscore how political events can be framed differently, influencing public perception and political opinion.